Pesan Islam Moderat Dalam Buku “Tuhan Ada Di Hatimu” Karya Habib Husain Ja’far Al Hadar - Nangim Yunus; Sayidah Afyatul Masruroh (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2023)
God's book is in your heart containing the views of various things from the beautiful Islamic point of view including the current conditions, all of that can be answered with the teachings of Islam as a religion that is timeless. Therefore, this research was carried out to identify any da'wah messages contained in it book God is in your heart conveying the various contents of the messages in it according to life's problems from various aspects through the da'wah it conveys so that it can be taken as research material in this thesis. Until in this research the researchers formulated the research focus in this thesis, namely: (1) What is the message of moderate Islam contained in Habib Husain Ja'far al Hadar's book God Is in Your Heart. The theory used in this study is Content analysis for R Holsti, is a method for drawing conclusions by identifying the various special characteristics of a message objectively and systematically. The method used in this study is content analysis context analysis through a qualitative approach using descriptive analysis techniques. Analysis of the contents of the context of research analysis and intended fo examine the contents of the message and equate it in a communication during the da'wah messages in each paragraph which consists of four sub-titles of one book. Based on the results of the data received is that the contents of God's book are in your heart, there are many messages of aqidah da'wah which contain teachings to believe in Allah and there are messages of moral preaching related to how we should behave towards fellow human beings, the da'wah messages in God's book are in your heart very relevant to everyday life because da'wah messages are packed with analogies that often occur in our daily lives. Keyword: Moderate Islam, the book